Relasi Gender Pasangan Keluarga Disabilitas dalam Perspektif Islam Studi Kasus di Perhimpunan Tunanetra Indonesia NTB - Dhevia Nursafitri (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2024)
The background for the emergence of the domestic and public areas comes from the division of labor based on sex, which is more popularly known as gender. The concept of gender refers to a set of traits, roles and responsibilities, functions, rights and behaviors inherent in men and women that cannot be separated from the culture that is built in the society where humans grow and develop so that a masculine dichotomy arises (male and female). ) and feminine (female). This study aims to find out about how the division of domestic and public tasks and family resilience in disabled family couples with non-disabled blind people. The approach used in this study is a qualitative approach. The data collection technique used observation and interview techniques. The validity of the data was by increasing the research time, adequacy of references, triangulation and peer examination. The results of this study indicate that non-disabled blind spouses with husbands with visual impairments in the division of roles in the public area are carried out by both the wife and husband, while in the domestic area only the wife is involved, while the spouses with blind disabilities and non-disabled husbands are blind in the area. in the public sector only done by the husband while in the domestic area only done by the wife. There are several factors behind the strong family resilience of non-disabled spouses and husbands with disabilities including: flexibility, good communication, family support and spirituality, and a good economy, while the factors behind the weak family resilience of disabled spouses with non-disabled husbands Disabilities include: weak commitment to Islamic values, weak economy, lack of communication between family members, weak problem-solving abilities, and no support from family.